Safety and Efficacy of Thalidomide in Children with Transfusion Dependent Thalassemia: A Quasi Randomized Control Trial in a Tertiary Care Hospital in Bangladesh - Hasan, Md Mehedi; Karim, Md Anwarul; Rahman, ATM Atikur; Jamal, Chowdhury Yakub; Paul, Soumitra; Akther, Farah; Rahman, Rezwana; Rahman, Moklesur (Bangladesh Journal of Medicine, 2026)
Background: Thalidomide has been shown as a promising treatment option for reducing transfusion volume in adults with β-thalassemia. It induces γ-globin expression in erythroid progenitor cells, but its efficacy on children with transfusion-dependent β-thalassemia (TDT) remains unclear. This study aimed to determine the safety and efficacy of thalidomide in TDT children. Methods: In this phase 2, single-center, quasi-randomized, single-blind clinical trial, 60 patients of 3-18 years were randomly assigned to receive placebo or thalidomide for 12 weeks. The primary endpoint was the change of hemoglobin (Hb) level in the patients. The secondary endpoints included the red blood cell (RBC) units transfused and adverse effects. Results: In the placebo-controlled period, Hb concentrations in patients treated with thalidomide achieved a median elevation of 14.5 (range, 5.0 to 34.0) g/L, whereas Hb in patients treated with placebo did not significantly change. Within the 12 weeks, the mean RBC transfusion frequency for patients treated with thalidomide and placebo was 0.73 ± 0.9 times and 2.9 ± 0.6 times, respectively (P < 0.001). Significant increase in Hb concentration and reduction in RBC transfusions were associated in children with E-β Thalassemia in comparision with β-thalassemia major (P < 0.001). No unfavorable efects were observed on kidney and liver functions. Mild adverse events including drowsiness, dizziness, pyrexia, pruritus, abdominal pain, nausea, constipation, facial edema were more frequently found in (60%) patients treated with thalidomide. Conclusion: This study concludes that thalidomide is an efective and well-tolerated drug that can significantly increase Hb levels and reduce transfusion burden in children with TDT patients. Bangladesh J Medicine 2026; 37(2): 100-105